SISTEM PEMBALIKAN BEBAN PEMBUKTIAN TINDAK PIDANA PENCUCIAN UANG DITINJAU DARI ASAS HUKUM PIDANA DI INDONESIA - Fahd Akbar, mochammad (Irtifaq, 2019)
The reversal of the burden of proof is applicable in Law Number 8, 2010 about Prevention and Eradication of Money Laundering Crime in Article 77. This does not violate the principle of criminal law in Indonesia, because the rights in the trial of the suspect or defendant are not reduced by the proof system. It is not unreasonable if the reversal system of the burden of proof is contrary to the criminal law principle in Indonesia. This is for the collective interest to the rights of the society and the state integrity which is now in the spotlight and the declining condition due to the numerous criminal acts that are specific such as corruption and money laundering is increasingly massive. Regarding the expropriation of property which is not the result of a crime but has already been confiscated, the law here provides an opportunity for the defendant that the property has been confiscated but not related to the money laundering crime. By filing a pre-trial be arranged in Article 77 until Article 83 The Criminal Code Procedure. If the court believes that the property or asset being confiscated are not connected nor the results of the indicted crime, then the court may order to return the property or asset has already been confiscated to defendant or to the rightful. Keywords: Reversal System of the Burden of Proof Money Laundering Crime